A new method of multi-robot cooperative exploration. (14th November 2022) - Wang, Yanqing; Li, Yongquan; Lu, Wenjun
This paper aims at the task of the map fusion and environmental exploration method. The multi-robot collaborative map creation is based on the local map by each individual robot, and the nodes in the local map are matched to obtain the association between multiple maps. Multi-robot task allocation is also a process of maximising the benefits of resource utilisation. How to allocate resources reasonably so that each robot can quickly complete the corresponding tasks in coordination, and how to solve the problem of the heavy tasks for individual robots or few tasks for individual robots, multitask allocation based on market law can be a solution. The new topological scene map in this paper is used to represent the environment and carry out robot exploration. It can be seen that multi-robot cooperative exploration is more efficient efficiency.